Kontrasty, deformacje, demontaże. Literackie przetwarzanie form nieliterackich w literaturze polskiej po 1956 roku - Bukowiecka, Marta (Zagadnienia Rodzajów Literackich, 2019)
The text concerns the expansion of non-artistic forms of language in Polish literature after the “Polish thaw”. They are separated from real context, processed in an experimental, radical and original way and (re)used in the literary work as linguistic, ready-made objects or as a part of artistic recycling. I point out three strategies of language processing: contrasting, deforming and dismantling, which are present in works by three post avant-garde writers: Leopold Buczkowski, Tadeusz Różewicz and Miron Białoszewski. Striving for innovation and experiment, thinking of language with growing suspicion, focusing on its tendency to petrification allows their work to be seen as the continuation of modernist tendencies.